PENERAPAN MODUL AJAR BERBASIS SCIENTIFIC APPROACH BERBANTUAN LKPD UNTUK MENINGKATKAN KETERAMPILAN MENULIS REPORTASE SISWA KELAS III SD: Penerapan Modul Ajar LKPD - Henning Puspa Rini; Annisa Rizqi Pratiwi; Afni Khalistania Dewi; Panca Dewi Purwati (STKIP Subang, 2025)
This study examines the effectiveness of a Scientific Approach–based teaching module supported by Student Worksheets (LKPD) in improving the report-writing skills of third-grade elementary students. The study addresses the low ability of students to organize factual information and produce coherent report texts. Using a mixed-methods convergent parallel design, the research involved 18 students, with quantitative data collected through pretest–posttest and qualitative data through observations, interviews, and student response questionnaires. Results show a substantial improvement, with the mean score increasing from 56.5 to 79.5 and an N-Gain of 0.62 categorized as medium–high, indicating the module’s effectiveness. Qualitative findings reinforce this outcome, revealing that LKPD provided structured guidance that facilitated the implementation of Scientific Approach stages—observing, questioning, data collecting, associating, and communicating—and that most students (88–94%) reported positive experiences, stating that LKPD supported their progression from concrete observation to structured text writing. Overall, the module effectively functions as systematic scaffolding for enhancing both the learning process and the quality of report writing among third-grade students.